Creating a locally driven research agenda for the ethnic minorities of Eastern Myanmar - Purkey, Eva (Health Res Policy Syst, 2019)
BACKGROUND: Research funding and production is inequitably distributed internationally, with emphasis placed on the priorities of funders and international partners. Research capacity development, along with agenda-setting for research priorities can create agency and self-sufficiency and should be inclusive of all relevant stakeholders. Myanmar is a fragile state, where decades of conflict have created a weakened healthcare system and health research sector. The population of Eastern Myanmar have long had their healthcare needs met by community-based organisations and ethnic health organisations operating within Eastern Myanmar and the adjoining Thai–Myanmar border. Despite a transition to civilian rule, the current context does not allow for a truly participatory health research capacity development and agenda-setting exercise between the health leaders of Eastern Myanmar and the government in Yangon. In this context, and with a desire to enhance the capacity, legitimacy and agency of their organisations, the health leaders of Eastern Myanmar are seeking to develop their own health research capacity and to take control of their own research agenda. METHODS: Approximately 60 participants from 15 organisations attended a 3-day forum with the goals of (1) developing research capacity and interest through a research conference and methods workshop; (2) using a nominal group technique (NGT) to develop a locally driven research agenda; and (3) supporting the development of local research projects through ongoing funding and mentorship. RESULTS: Participants were actively engaged in the workshops and NGT. Participants identified a broad range of health issues as priorities and were able to develop consensus around a list of 15 top priorities for the populations they serve. Despite availability of ongoing support, participants did not pursue the opportunity to engage in their own research projects emerging from this forum. CONCLUSIONS: The NGT was an effective way to achieve engagement and consensus around research priorities between a group of healthcare providers, researchers and policy-makers from a variety of ethnic groups. More active involvement of senior leadership must happen before the energy harnessed at such a forum can be implemented in ongoing research capacity development.